Discovery and Biosynthesis of a Structurally Dynamic Antibacterial Diterpenoid. Issue 25 (14th May 2021) - Zhu, Chenxi; Xu, Baofu; Adpressa, Donovon A.; Rudolf, Jeffrey D.; Loesgen, Sandra
Abstract: A new bicyclic diterpenoid, benditerpenoic acid, was isolated from soil‐dwelling Streptomyces sp. (CL12‐4). We sequenced the bacterial genome, identified the responsible biosynthetic gene cluster, verified the function of the terpene synthase, and heterologously produced the core diterpene. Comparative bioinformatics indicated this Streptomyces strain is phylogenetically unique and possesses nine terpene synthases. The absolute configurations of the new trans ‐fused bicyclo[8.4.0]tetradecanes were achieved by extensive spectroscopic analyses, including Mosher's analysis, J ‐based coupling analysis, and computations based on sparse NMR‐derived experimental restraints. Interestingly, benditerpenoic acid exists in two distinct ring‐flipped bicyclic conformations with a rotational barrier of ≈16 kcal mol −1 in solution. The diterpenes exhibit moderate antibacterial activity against Gram‐positive bacteria including methicillin and multi‐drug resistant Staphylococcus aureus . This is a rare example of an eunicellane‐type diterpenoid from bacteria and the first identification of a diterpene synthase and biosynthetic gene cluster responsible for the construction of the eunicellane scaffold. Abstract : We report the isolation of an eunicellane‐type diterpenoid from bacteria and the first identification of a diterpene synthase and biosynthetic gene cluster responsible for the construction of the eunicellane scaffold. The absolute configurations and antibacterial activities of benditerpenoic acid and the benditerpe‐2, 6, 15‐triene core were established.